THE ROLE OF PRODUCER IN THE PRODUCTION OF DOCUMENTARY TELEVISION PROGRAM "WISATA MUSLIM NUSANTARA" - Kusuma, Nanda Jati; Tahapary, Hanoch (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
This research aims to study the role of producer in the production of documentary television program "Wisata Muslim Nusantara". This program aims to explore and introduce the potential of Muslim tourism in various regions in Indonesia. This research uses a qualitative approach with in-depth interviews with the program producer and content analysis of the resulting television program. The results showed that the producer's role includes planning, organizing, supervising, and controlling all stages of program production. Producers are responsible for developing program concepts, determining goals and target audiences, and managing production schedules and budgets. In addition, the producer also plays a role in conducting research, selecting locations, and building cooperation with related parties such as local governments, Muslim communities, and the tourism industry. Producers are also involved in the content production process, including scriptwriting, shooting, editing and sound production. In terms of distribution, producers play a role in establishing cooperation with television stations to air the program, as well as promoting the program through social media and other online channels. Producers are also involved in evaluating and improving the program based on responses and feedback from viewers. The success of the program depends not only on informative and interesting content, but also on the producer's ability to manage and direct the entire production process.